Sports, Health and Exercise Medicine - Honório, Samuel; Batista, Marco; Serrano, João; Silva, Maria-Raquel G. (IntechOpen, 2020)
This book presents a diversity of themes written by authors related to sports medicine and health varying from clinical issues, such as sports injuries to specific neuropsychological aspects of the athletes' behaviour regulation and parathletes' motivation for sport practice.This comprehensive volume is very appealing, which will also be recognised by Sports and Health Professionals, who need further support in their daily work with athletes and coaches, in particular. It is also attractive to researchers and students interested in sport and health related areas.